Northern Irish Writing After the Troubles Intimacies, Affects, Pleasures - Magennis, Caroline (New Horizons in Contemporary Writing, 2021)
Winner of the British Association for Comtemporary Literary Stuides (BACLS) monograph prize The period since the Good Friday Agreement in 1998 has seen a sustained decrease in violence and, at the same time, Northern Ireland has undergone a literary renaissance, with a fresh generation of writers exploring innovative literary forms. This open access book explores contemporary Northern Irish fiction and how the 'post'-conflict period has led writers to a renewed engagement with intimacy and intimate life. Magennis draws on affect and feminist theory to examine depictions of intimacy, pleasure and the body in their writings and shows how intimate life in Northern Ireland is being reshaped and re-written. Featuring short reflective pieces from some of today's most compelling Northern Irish Writers, including Lucy Caldwell, Jan Carson, Bernie McGill and David Park, this book provides authoritative insights into how a contemporary engagement with intimacy provides us with new ways to understand Northern Irish identity, selfhood and community. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.